What caused the strong increase of the winter population of the Dalmatian Pelican, Pelecanus crispus, in Iran in the last two decades?. Issue 4 (2nd October 2019) - Ashoori, Abbas; Amini, Hamid; Khaleghizadeh, Abolghasem; Manolopoulos, Aris; Catsadorakis, Giorgos
Abstract : The Dalmatian Pelican Pelecanus crispus is listed globally as "Near Threatened". We used the results of the International Waterbird Census from 1998 to 2017 to find trends in wintering numbers. Of the 102 sites examined, 29 were classified as regular, 18 as irregular and 55 as occasional wintering habitats for the species. Both the population size and the geographical distribution increased in the second half of the study period. The Anzali Wetland Complex, Gomishan Marsh, Gorgan Bay and Miankaleh Wildlife Refuge, inlets and mangroves east of Jask, the east coast of Chabahar and inlets and mangroves west of Konarak were identified as the most important wintering areas of the Dalmatian Pelican in Iran. Wintering numbers increased from 300 to 1, 100 in the 1970s and from c. 800 in the 1980s to c. 1, 800 by 2006 and up to c. 10, 000 in 2017. Thus, more than 37% of the global population of the species overwinters in Iran. A combination of a series of warm winters and delayed timing of cold spells appears to be responsible for the increase of the wintering population.